Menguji Ketajaman Implementasi E-Commerce Dalam Penjualan Kamar Hotel di Bali - Ni Made Widani; Agus Putu Abiyasa; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThe concept of a market provider of room rentals or residential units using online networking information technology systems to increase the hotel revenue & also effective strategy to comfit offline strategy in the hotel industry. It is still unclear whether the implementation of e-commerce are work in all hotel strategy in the develop hotel revenue in the hotel industry. The purpose of this study is to analyze the fenomena average rooms rate (ARR) in Holiday Inn Express Bali which using standard operation procedure worldwide, International Hotel Group (IHG) which compare than other country still low especially in Asia Pacific area while location wise and company strategy is part of the factor issues & also price war happen in Bali market which need government policies in addressing the development of the hotel industry. This research used qualitative method that is constructive with literature review and documentation as the premier data source. The results of the study cover the advantages and disadvantages of the existence of online market places for Holiday Inn Express in Bali especially and in the hotel industry generally. This research of e-commerce is contributes to the hotel industry to generate & develop the revenue. To maximize the online source in generate revenue the hotel strategy need to hire special person incharge to taking care the tasking of online market needs to bush the hotel occupancy and also yielding with average room rate, while standardization of the quality of rooms or residences are also the important leased needs to be done to ensure the quality of the products and services offer as well, especially in online market place. Further studies can be conducted to analyze the sales & marketing strategy using e-commerce (online travel agents) which hotel should always pro active to make special offer to genereate last minute booking base on occupancy daily facing & at least one or two week  before promotion progress and also advance purchace strategy like minimum 6 months booking costumer will get special rate, rooms inventory monitor and maintain good communication with maintain relationship by consider their production ( like review top 10 production in a month) will feel the appreciation from all online agents partner are the best strategy to achieve company expectation.